2014
DOI: 10.1039/c3cc48555b
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective functionalization of 2-arylazetidines: evaluating the ortho-directing ability of the azetidinyl ring and the α-directing ability of the N-substituent

Abstract: The regioselective lithiation-functionalization of 2-arylazetidines has been explored. The nature of the N-substituent is mainly responsible for a regioselectivity switch. ortho-Lithiation occurred, using hexyllithium as a greener base, in N-alkylazetidines, while α-benzylic lithiation has been observed with N-Boc azetidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…First, we investigated the reactivity of 1‐methyl‐2‐phenylazetidine ( 1 a ), chosen as a reference substrate, towards bases other than n ‐hexyllithium ( n HexLi). We found that n HexLi was effective in the regioselective ortho ‐lithiation of 1 a under very mild conditions 9a. Nevertheless, as reported in Table 1, other organolithium reagents and lithium amides were taken into consideration for two main reasons: 1) to explore the possibility to switch the regioselectivity (i.e.…”
Section: Resultssupporting
confidence: 58%
“…First, we investigated the reactivity of 1‐methyl‐2‐phenylazetidine ( 1 a ), chosen as a reference substrate, towards bases other than n ‐hexyllithium ( n HexLi). We found that n HexLi was effective in the regioselective ortho ‐lithiation of 1 a under very mild conditions 9a. Nevertheless, as reported in Table 1, other organolithium reagents and lithium amides were taken into consideration for two main reasons: 1) to explore the possibility to switch the regioselectivity (i.e.…”
Section: Resultssupporting
confidence: 58%
“…However, just few examples on this topic have been reported mainly by Seebach on azetidines with an electron-withdrawing group (EWG) as the Nsubstituent such as N-nitrosoazetidine and N-(triphenylacetyl)azetidine (Scheme 26). [66] N-Methyl-2-arylazetidines were smoothly ortho-lithiated upon treatment at 20°C with n-HexLi in the presence of TMEDA (Scheme 28). [64] complished, leading to azetidines 108a,b although in low yield, only by using in situ-quenching conditions and performing the deprotonation reaction of 107 with n-hexyllithium (n-HexLi) in 2-MeTHF at -84°C (Scheme 27).…”
Section: Lithiated Arylazetidinesmentioning
confidence: 99%
“…[7][8][9][10] A common limitation of these approaches is that they often require functional-group installation prior to azetidine formation. [11,12] We wondered whether simple access to azetidine nitrones could provide an opportunity for the development of simple functionalization strategies to access highly substituted examples of these strained ring systems from ac ommon unsaturated intermediate.…”
mentioning
confidence: 99%